An Investigation into the Application of Humanistic Approach: a Case-study undertaken in a Chinese Company - Liang, Enqi (International Journal of Global Economics and Management, 2024)
Chinese human resource manages are looking for new ways to manage workforce because of increasing employee turnover. The humanistic management approach may be useful for Chinese managers and companies. However, few qualitative studies have explored the views of Chinese enterprises towards humanistic management approach. The research aims to investigate the perspectives and experiences of managers on the introduction of humanistic management approach into a Chinese Company in-depth. Semi-structured Interviews were conducted with two managers participated in work for a technology company known for its people-oriented management. The results demonstrated that The implementation of people-oriented management in the research company is mainly reflected in the corporate culture and employee welfare. Its main advantages include co-development and freedom of expression. However, the underlying concerns of the humanistic approach lie in low motivated employees and unfairness. These factors should be considered in the development of humanistic management approach to increase the applicability from Chinese companies.